Kecenderungan Pemilihan Jajanan pada Anak Usia Sekolah di MI Darul Ulum Kecamatan Ngaliyan Kota Semarang - Nur Hayati; Hilmah Nuriya (Jurnal Gizi, 2018)
Snacks are foods used by school children even for school children to buy snacks. The quality of many snacks on the market is still increasing the monitoring of the adequacy of nutritional value for children who are in growth. Children's snacks these days have become worthwhile because there are sellers who are not responsible for chemicals such as formaline, borax, textile dyes, and artificial sweeteners. The attitude of the child in choosing a snack can affect his health. Children who do not have sufficient knowledge that healthy, safe, and halal gamblingoften consume snacks because of the fascinating charm to attract the attention of the food. The data used to determine the tendency of hawker election in children who already have knowledge abouthealthy food. The sample used as the data at this time is all Class V (five) MI Darul Ulum District Ngaliyan City Semarang, as many as 43 respondents. Data collection using techniques, interviews and questionnaires. Test the validity of the questionnaire using product moment and reliability using alpha cronbach. Knowledge given and donation of 18.06% to the tendency in choosing snacks at Class V students (five) MI Darul Ulum Ngaliyan Subdistrict Semarang City.Keywords: healthy food knowledge, tendency to choose, snacks, childrenschool